Prevalence of Type 2 Diabetes in pediatrics and adolescents newly diagnosed with diabetes in Babylon Governorate, Iraq - Yasameen Alsaffar (Archivos Venezolanos de Farmacología y Terapéutica, 2020)
Type 2 diabetes in children and adolescents is a rising and ongoing problem around the world. It has adverse medical and economic consequences, and it is underestimated in many countries. Highlight characteristics of children presented with type 2 diabetes, and estimate the prevalence of such type of diabetes among newly diagnosed pediatrics. A total of 253 children and adolescents were diagnosed with diabetes. A thorough history and complete physical examination were done on all patients. Patient’s samples were sent for assessment of serum C peptide levels and glycated haemoglobin (HbA1c). 16 out of 253 newly diagnosed patients with diabetes have been found to have type 2 diabetes (proportion was 6.32%) with a mean age of 14.78 ± 2.87. All 16 patients had a positive family history and high body mass index, which significantly differ from type 1 diabetes patients. Also, all showed acanthosis nigricans and higher C-peptide levels than type1 patients (P=0.0001). Most children and adolescents with type 2 diabetes are obese or overweight, and many show features of insulin resistance. Every effort should be done to differentiate type 2 diabetes from the most common type 1 diabetes in young people.